GROUND WATER ASSESSMENT IN AGRICULTURAL AREA, CASE STUDY FROM MACHANG-MALAYSIA (Penilaian Air Tanah di Daerah Pertanian, Studi Kasus di Machang Malaysia) - Nur Islami (Jurnal Manusia dan Lingkungan, 2010)
ABSTRACTThe study area is located in Machang, North Kelantan - Malaysia. The North Kelantan plain is covered with Quaternary sediments overlying granite bedrock. The drainage system is dendritic with the main river flowing into the South China Sea. Hydrogeochemical method was used to study groundwater of shallow aquifer characters within the area. Based on water samples analysis collected from the study area, it can be deduced that the cations and anions concentration are good for domestic use except in the southern region which the nitrate concentration is higher (more than 20 mg/l) compared to the northern region (relatively zero). The areas that possibly possess nitrate-contaminated groundwater have been mapped along with groundwater flow patterns. The southern and middle part of the study area has an east to west groundwater flow pattern, making it impossible for contaminated water from the southern region to enter the northern area, despite in the northern area has lower elevation.ABSTRAKLokasi area studi adalah berada di Machang, Kelantan Utara – Malaysia. Dataran tanah wilayah Kelantan Utara dilapisi oleh batuan Sedimen Kuarter yang mana batuan granit sebagai batuan dasar. Sistem pengairan adalah berbentuk jaringan dendritik dengan sungai utama mengalir ke Laut Cina Selatan. Metoda hydrogeochemical digunakan untuk mempelajari karakter air tanah dari akuifer dangkal untuk keseluruhan area studi. Berdasarkan pada analisa air yang diperoleh dari area studi, dapat disimpulkan bahwa konsentrasi kation dan anion baik digunakan untuk kehidupan sehari hari kecuali air tanah di area sebelah selatan yang mana kandungan nitratnya tinggi (lebih dari 20 mg/l) dibandingkan di area sebelah utara (hampir tidak ada kandungan nitrat). Area yang memungkinkan memiliki konsentrasi nitrat pada air tanah dipetakan dengan kombinasi pola aliran air tanah. Pola aliran air tanah di area belahan selatan dan bagian tengah adalah dari timur ke barat yang mana tidak memungkinkannya air tanah yang terkontaminasi oleh nitrat di belahan selatan untuk masuk ke area belahan utara walaupun di belahan utara adalah dataran rendah.